2005
DOI: 10.1641/0006-3568(2005)055[0399:tdiuc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Dynamics in Urban Communities

Abstract: Articles Ecologists have long debated what factors control the trophic (feeding) structure and function of ecosystems. This is more than just a matter of determining "who eats whom"; ecologists have pondered whether there are fundamental rules for determining (a) how many trophic levels an ecosystem can support, (b) how much primary production is consumed by herbivores, and (c) whether resources from the bottom of the food chain, or consumers from the top, control biomass, abundance, and species diversity in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
353
3
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(365 citation statements)
references
References 52 publications
4
353
3
5
Order By: Relevance
“…Urban development creates new opportunities and challenges for species competition and predation, both as exotic species are introduced and as invasive species migrate in, taking advantage of poorly integrated communities and patches. This might result in colonization, as more frequent introductions of exotic species translate into invasions (23). For example, McDonnell and Hahs (24) found higher levels of earthworm biomass and abundance in urban forests compared with rural ones, likely because of introduced species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban development creates new opportunities and challenges for species competition and predation, both as exotic species are introduced and as invasive species migrate in, taking advantage of poorly integrated communities and patches. This might result in colonization, as more frequent introductions of exotic species translate into invasions (23). For example, McDonnell and Hahs (24) found higher levels of earthworm biomass and abundance in urban forests compared with rural ones, likely because of introduced species.…”
Section: Discussionmentioning
confidence: 99%
“…We used an information-theoretic approach to rank statistical models and conduct multimodel inference, based on AICc (23,55). AICc favors model fit (minimizing deviance) while avoiding model overfitting (penalizing for the number of estimated parameters, K ), and was the basis for enforcing the parsimony principle given our sample sizes (1,663 rates nested in 175 study systems).…”
Section: Methodsmentioning
confidence: 99%
“…Variation in responses within and between trophic groups may cause restructuring of communities through changes in competitive, bottom-up and top-down control effects (Van der Putten et al 2004). Any given species is affected by interactions with other species, therefore understanding how changes in species interactions potentially affect food web structure and function in urban habitats may help us to succeed when planning conservation strategies (Faeth et al 2005;Faeth et al 2011). To our knowledge, our work presents the first effort to address how interrelated multi-trophic interactions composed by herbivory, predation, parasitism and mutualism behave in urban habitats, with predation the most affected by the increase of urban features in the habitat.…”
Section: Discussionmentioning
confidence: 99%
“…There are also some dramatic physical changes from increased densities of roads, buildings and other sealed structures and microclimatic changes such as the urban heat island effect (Bradley and Altizer 2007;Faeth et al 2011). Together, these changes affect the likelihood of encountering species at higher trophic levels (Faeth et al 2005;Egerer et al 2017). Understanding how such extreme anthropogenic habitat changes may affect patterns of ecological interactions is perhaps most tractable with arthropod model systems (McIntyre 2000;Bang and Faeth 2011), but experimental studies in urban ecosystems are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…During this time, approximately 680,000 ha of rural land were converted to developed uses annually (USDA NRCS, 2007). Net loss and fragmentation of rural lands have many potential implications for the goods, services, and functions of natural resources provided by such landscapes (e.g., Alberti et al, 2003;Arnold and Gibbons, 1996;Collins et al, 2000), the species that use them and their habitat (e.g., Faeth et al, 2005;McKinney, 2002;Riley et al, 2003), and the ability of invasive species to establish themselves (e.g., Holway, 2005;Lambropoulos et al, 1999;Yates et al, 2004). Past research also has suggested that the addition of homes and other structures into rural landscapes can increase the probability of wildland fire and complicate fire management efforts (e.g., Berry and Hesseln, 2004;Cardille et al, 2001;Gebert et al, 2007;Sturtevant and Cleland, 2007), can have deleterious effects on water quality (Atasoy et al, 2006;Pijanowski et al, 2002b;Tang et al, 2005), and possibly can reduce the propensity for forest management and timber harvest Munn et al, 2002;Wear et al, 1999).…”
Section: Introductionmentioning
confidence: 99%